Integrated Bidirectional DC-DC Energy Storage Low-floor Trams Traction System - Yuan Wenye; Chen Wenguang; Xia Wenjie; Lin Wenbiao; Zhang Lujun (机车电传动)
The vehicle parameters and performance requirements of integrated bidirectional DC-DC energy storage low-floortrams traction system were introduced, and the traction system traction/braking characteristics, system composition, system matchingcontrol strategy were expounded. Energy storage low-floor trams traction system was composed of traction inverter, bidirectional DCDCconverter and the storage system. The traction inverter and bidirectional DC-DC converter integrated in the main converter met theapplication of traction-braking, overhead lines segment or no overhead lines segment and a variety of operating conditions.